2021
DOI: 10.7189/jogh.11.05027
|View full text |Cite
|
Sign up to set email alerts
|

A rapid review of evidence on the determinants of and strategies for COVID-19 vaccine acceptance in low- and middle-income countries

Abstract: Background Vaccine acceptance and hesitancy among the general population and health care workers play an important role in successfully controlling the Coronavirus Disease (COVID)-19 pandemic. While there is evidence for vaccine hesitancy across the globe, wide variation in factors influencing vaccine acceptance has been reported, mainly from High-Income Countries (HIC). However, the evidence from Low- and Middle-Income Countries (LMICs) remains unclear. The objective of this review was to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
82
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 36 publications
19
82
2
2
Order By: Relevance
“…Trust in vaccines and vaccine messaging: Accurate and reliable information on the safety and effectiveness of COVID-19 vaccines will need to be made available to populations in these countries through a variety of trusted channels and leaders to increase COVID-19vaccine acceptance [40][41][42]. A lack of trust in COVID-19 vaccines was common among Non-acceptors in all five countries where it was assessed (Bangladesh, Kenya, Myanmar, the DRC, and Tanzania).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust in vaccines and vaccine messaging: Accurate and reliable information on the safety and effectiveness of COVID-19 vaccines will need to be made available to populations in these countries through a variety of trusted channels and leaders to increase COVID-19vaccine acceptance [40][41][42]. A lack of trust in COVID-19 vaccines was common among Non-acceptors in all five countries where it was assessed (Bangladesh, Kenya, Myanmar, the DRC, and Tanzania).…”
Section: Discussionmentioning
confidence: 99%
“…Information will need to be disseminated to counter (but not repeat) common myths about the vaccines' safety and effectiveness, such as beliefs in the DRC and Myanmar that the vaccines have negative and potentially deadly side effects and beliefs about the vaccines causing impotence in Tanzania. Perceived safety and trust in COVID-19 vaccines and in those promoting the vaccines (e.g., health workers and government workers) have been found to be important determinants of COVID-19 vaccination in other countries [42].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review about the reasons for vaccine hesitancy in LMICs showed that exposure to misinformation about COVID-19 vaccines, public concerns over the safety of vaccines, and distrust in the government, were the main contributing factors to low vaccine acceptance rates [18]. Therefore, to decrease vaccine hesitancy, direct engagement with communities through influencers, including community leaders and health experts, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a very large number of studies addressing COVID-19 vaccine acceptance among adults [18], there is a limited number of studies examining COVID-19 vaccine acceptance for children especially among low-and middle-income countries (LMICs) [19][20][21]. Given the feasibility of vaccinating children in LMICs with the COVID-19 vaccine in the near future, our research questions were: (1) What are the COVID-19 vaccine acceptance rates for children at 50%, 75%, and 95% effectiveness levels, and (2) What are the factors affecting vaccine acceptance for children?…”
Section: Introductionmentioning
confidence: 99%
“…However, we are unaware of comprehensive categorizations and confirmations of these factors and their effects. Earlier reviews have focused on summarizing global vaccine hesitancy rates [ 13 ], calculating global vaccine acceptance rates [ 23 ], pooling vaccine acceptance rates and their predictors [ 5 ], describing vaccine acceptance rates among LMICs in a qualitative fashion [ 24 ], scoping vaccine acceptance rates in higher-income countries [ 25 ], or scoping vaccine hesitancy rates and their predictors [ 26 ]. A systematic review with a meta-analysis of vaccine acceptance and hesitancy rates and their associated factors in LMICs has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%